Early career patterns : a comparison of Great Britain and West Germany - Scherer, Stefani [Verfasser] (My University, 2001)
"The transition from initial education to work has received a great amount of attention, but hardly any research treats this process holistically. This paper focuses on the serial succession of statuses instead of on single events in the early years after leving full-time education. As a methodological tool sequence analysis will be applied. Optimal matching procedures allow for the direct comparison of entire career sequences taking into account the ordering of the events. The objective of applying this rather new tool is to empirically identify distinct patterns of transition into the labour market. The analysis covers the whole range of employment statuses including periods of unemployment and inactivity that individuals experience within the first five years following completion ofo education. A cross-national comparison between Great Britain and West Germany aims at investigating to what extent the observed patterns of transition processes are shaped by their institutional embeddedness." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2 Arbeitsmarkt; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; P 2.1.5 Fachhochschul- und Hochschulreife; I 2.1.2 Alte Bundesländer; I 2.2.1 Westeuropa; Berufsausbildung; Absolvent; Berufseinmündung; Internationaler Vergleich; Erwerbsverhalten; Geschlechtsspezifische Faktoren; Ausbildungsabschluss; Hochschule; Quantitative Angaben; Westdeutschland; Großbritannien; 1985-1989